Journal of Applied Spectroscopy - Borisevich, Nikolai A.; Kilin, S.Ya.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Journal of Applied Spectroscopy reports on many key applications of spectroscopy in chemistry, physics, metallurgy, and biology. An increasing number of papers focus on the theory of lasers, as well as the tremendous potential for the practical applications of lasers in numerous fields and industries. Journal of Applied Spectroscopy is a translation of the Russian language journal Zhurnal Prikladnoi Spektroskopii. The Russian Volume Year is published in English from April. All articles are peer-reviewed.
Keywords: Analytical chemistry; Atomic structure; Molecular structure; Spectra; Atomic/Molecular Structure and Spectra; Analytical Chemistry